A Bibliometric Study on the Evolution of Portfolio Management Strategies - Judijanto, Loso; Sudarmanto, Eko (The Es Accounting And Finance, 2024)
This study conducts a bibliometric analysis of the evolution of portfolio management strategies from 1970 to 2023, aiming to trace key developments, emerging trends, and the impact of technological advancements on the field. By analyzing a dataset of 1,000 published papers, this research highlights significant theoretical contributions, such as Modern Portfolio Theory and the Capital Asset Pricing Model, while also identifying the growing importance of machine learning, artificial intelligence, and sustainability factors in portfolio management. The findings reveal a shift from traditional investment strategies to data-driven methodologies that integrate ethical considerations and ESG factors, reflecting the changing preferences of today’s investors. Additionally, the study emphasizes the need for an interdisciplinary approach and collaboration among researchers and practitioners to navigate the complexities of modern financial markets. The insights from this analysis provide valuable guidance for future research and practice in portfolio management, ensuring that strategies align with both financial objectives and broader societal goals.